Improving the efficiency of butter-making in Ethiopia - O'Connor, C.B.; Mezgebu, S.; Zewdie, Z. (1993)
Observations made of traditional butter-making by smallholders have indicated that the efficiency should be improved to save time, therby improving the economic return. Toward this end, the dairy technology personnel at the International Livestock Centre for Africa (ILCA) have developed a device that fits inside the traditional clay pot and rapidly and consistently agitates the milk. This internal agitator has passed through several phases of development over the years. Details on the design and construction of the agitator are given further on in this article. The dimensions may be amended to suit the size of the container used.